The Effect Of Dawood's Fasting In Removing Total Blood Cholesterol Levels In Surabaya Hidayatullah Islamic Boarding School’s Student - Rahayu, Indri Ngesti; Wijayanti, Ni Luh Putu Ratih; Purwaningsari, Diah; Komalasari, Intan; Dagradi, Eric Mayo (Jurnal Medis Islam Internasional, 2021)
Background: Hypercholesterolemia is a risk factor for causing death at a young age. The World Health Organization reported in 2002 that 4.4 million deaths were caused by hypercholesterolemia, or 7.9% of the total number of deaths at a young age. Hypercholesterolemia is a condition in which cholesterol levels in the body exceed normal levels. One way that can be done to prevent hypercholesterolemia is to control diet, namely by fasting. Dawood’s fasting is one of the obligatory fasts of Islamwhich is done with one-day fasting and one-day not. Objective: This study aims to determine the effect of Dawood’s fasting in reducing total blood cholesterol levels in Hidayatullah Islamic Boarding School students in Surabaya.Methods: This study was designed with a quasi-experimental study research method using a comparative pre-test post-test non-equivalent control group design. The sample in this study was divided into two groups, namely one control group and one treatment group from the sample selected by purposive sampling. The population studied were students of the Hidayatullah Islamic Boarding School in Surabaya. Result: The results of statistical analysis using the Wilcoxon signed-rank test showed an effect of Dawood’s fasting in reducing total blood cholesterol levels in Hidayatullah Islamic Boarding School students in Surabaya.Conclusion: From research result that has been done, it can be concluded that there is an effect of Dawood’s fasting in reducing total blood cholesterol levels in Hidayatullah Islamic Boarding School students in Surabaya. Keywords: Dawood’s fasting, total blood cholesterol.